Outcomes of an international workshop on preconception expanded carrier screening: Some considerations for governments - Molster, C.; Lister, K.; Metternick-Jones, S.; Baynam, G.; Clarke, A.; Straub, V.; Dawkins, Hugh; Laing, N. (2017)
© 2017 Molster, Lister, Metternick-Jones, Baynam, Clarke, Straub, Dawkins and Laing. Background: Consideration of expanded carrier screening has become an emerging issue for governments. However, traditional criteria for decision-making regarding screening programs do not incorporate all the issues relevant to expanded carrier screening. Further, there is a lack of consistent guidance in the literature regarding the development of appropriate criteria for government assessment of expanded carrier screening. Given this, a workshop was held to identify key public policy issues related to preconception expanded carrier screening, which governments should consider when deciding whether to publicly fund such programs.Methods: In June 2015, a satellite workshop was held at the European Society of Human Genetics Conference. It was structured around two design features: (1) the provision of information from a range of perspectives and (2) small group deliberations on the key issues that governments need to consider and the benefits, risks, and challenges of implementing publicly funded whole-population preconception carrier screening.Results: Forty-one international experts attended the workshop. The deliberations centered primarily on the c onditions to be tested and the elements of the screening program itself. Participants expected only severe conditions to be screened but were concerned about the lack of a consensus definition of "severe." Issues raised regarding the screening program included the purpose, benefits, harms, target population, program acceptability, components of a program, and economic evaluation. Participants also made arguments for consideration of the accuracy of screening tests.Conclusion: A wide range of issues require careful consideration by governments that want to assess expanded carrier screening. Traditional criteria for government decision-making regarding screening programs are not a "best fit" for expanded carrier screening and new models of decision-making with appropriate criteria are required. There is a need to define what a "severe" condition is, to build evidence regarding the reliability and accuracy of screening tests, to consider the equitable availability and downstream effects on and costs of follow-up interventions for those identified as carriers, and to explore the ways in which the components of a screening program would be impacted by unique features of expanded carrier screening.